2020
DOI: 10.3389/fpsyt.2020.00005
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Let Go: A Cognitive-Behavioral Model of How Psychedelic Therapy Promotes Acceptance

Abstract: The efficacy of psychedelic-assisted therapies for mental disorders has been attributed to the lasting change from experiential avoidance to acceptance that these treatments appear to facilitate. This article presents a conceptual model that specifies potential psychological mechanisms underlying such change, and that shows substantial parallels between psychedelic therapy and cognitive behavioral therapy: We propose that in the carefully controlled context of psychedelic therapy as applied in contemporary cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 102 publications
(159 reference statements)
9
99
0
5
Order By: Relevance
“…Indeed, observational study has identified a positive correlation between acutely challenging psychedelic experiences and long-term well-being, and at least one model of psychedelic efficacy proposes that overcoming difficult experiences through acceptance is of therapeutic benefit overall. [34,35] Interestingly, this model is consistent with stress inoculation effects seen in pre-clinical studies of anxious responding. [36,37] As the deliberate induction of challenging experiences through increases in environmental stressors or other manipulations are ethically impermissible in psychedelic clinical trials, this study proposes use of rodent models as an important means by which to potentially help resolve this issue.…”
Section: Introductionsupporting
confidence: 79%
“…Indeed, observational study has identified a positive correlation between acutely challenging psychedelic experiences and long-term well-being, and at least one model of psychedelic efficacy proposes that overcoming difficult experiences through acceptance is of therapeutic benefit overall. [34,35] Interestingly, this model is consistent with stress inoculation effects seen in pre-clinical studies of anxious responding. [36,37] As the deliberate induction of challenging experiences through increases in environmental stressors or other manipulations are ethically impermissible in psychedelic clinical trials, this study proposes use of rodent models as an important means by which to potentially help resolve this issue.…”
Section: Introductionsupporting
confidence: 79%
“…As such, moving from experiential avoidance to acceptance may play a key role in therapeutic outcomes associated with psychedelics. Therefore, we suggest that integrating psychedelics and psychotherapeutic interventions that specifically target experiential avoidance may help to enhance and prolong ( 93 ) the effectiveness of psychedelic therapy [for discussions, see ( 87 , 94 , 95 )]. Experiential avoidance is a primary target of ACT ( 26 ), an evidence-based psychotherapeutic intervention for a range of mental health problems [for a meta-analysis, see ( 96 )].…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapeutic models putting the psychedelic experience in a psychotherapeutic framework are now starting to be developed e. g., [149,150]. Whether the subjective experience has a therapeutic value in itself or should be regarded as an epiphenomenon of therapeutic neurobiological changes is still not agreed upon as the existing evidence is currently correlational in nature.…”
Section: The Subjective Psychedelic Experiencementioning
confidence: 99%